Evaluasi Kemiringan Jalan Tambang Terhadap Cycle Time Alat Angkut Pada Dump Truck Hino FG 235 JJ Tambang Batu Granit Di PT Aditya Buana Inter Kabupaten Bangka - Fitra Adreansyah; Franto Franto; E.P.S.B Taman Tono (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2023)
PT ABI is a private company engaged in the granite mining business using the open pit method. The problem encountered is that there is a slope of the mine road that does not comply with the standards set by the company, namely ≤ 8%, the slope of the mine road, which is not suitable, makes the truck to produce large rimpull, which affects the overall distribution time. This study aims to evaluate and optimize the dump truck cycle time obtained. This research begins by calculating the actual travel time on 2 dump trucks in 40 trips, conveyance A gets 493.72 seconds and conveyance B is 495.75 seconds, the actual travel time on the haul road segment exceeds ≥ 8%, i.e. in the B-C segment which has a grade of 8.86% with an average travel time of 20.38 seconds and in the C-D segment which has a grade of 10.51% with an average travel time of 37.91 seconds. Obtained circulation time decreased by 5 seconds from 494.73 seconds to 489.69 seconds with a percentage increase of 1.04% after optimization, meaning that the conveyance can transport 89 tons more of material.